A study on the effects of graphene nano-platelets (GnPs) sheet sizes from a few to hundred microns on the thermal, mechanical, and electrical properties of polypropylene (PP)/GnPs composites - Y-S. Jun; J. G. Um; G. Jiang; A. Yu (eXPRESS Polymer Letters)
Polypropylene (PP) is incorporated with four different grades (H100, M25, M5, and C300) of graphene nanoplatelets (GnPs) via twin screw extrusion followed by injection moulding. The composites’ thermal stability, crystallization behaviour, tensile strength, and electrical property are carefully examined. The thermal stability is significantly enhanced with the incorporation of small-sized GnPs as shown by the 11.2% improvement in T5% (the temperature at which 5 wt% of the mass loss occurs) and 5.1% improvement in Tmax (the temperature at which the maximum loss rate occurs). The thermal stabilizing effect of fillers can be significantly enhanced when they are well distributed with less aggregation as is the case for small-sized GnPs. The GnPs show a considerable nucleating effect on PP by increasing the crystallization temperature (Tc). The greatest improvement in tensile property is achieved with the use of small-sized GnPs. A 33.0% enhancement in tensile strength and 59.1% improvement of tensile modulus are obtained with the use of C300 and M5, respectively. The significantly increased thermal stability and mechanical property with small-sized GnPs are due to the fact that these smallsized fillers achieve a high degree of dispersion with less agglomeration as shown in the scanning electron microscope (SEM) images. However, the fillers with a large sheet size are still beneficial for purposes concerning electrical conductivity since the lowest percolation is obtained with H100. The greater the size of the GnPs, the smaller the percolation threshold of composites is exhibited.